From West to North Frisia. A Journey along the North Sea Coast Frisian studies in honour of Jarich Hoekstra - Walker, Alastair; Hoekstra, Eric; Jensma, Goffe; Vanselow, Wendy; Visser, Willem; Winter, Christoph (NOWELE Supplement Series, 2022)
This volume contains 25 articles covering a wide array of subjects, reflecting the breadth of scholarship of one of today's leading experts in the field of Frisian Studies. The articles, written mostly in English and German, encompass a temporal range from Old Frisian to Modern Frisian and a geographical range from West Frisian in the Netherlands to Sater and North Frisian in Germany, and include Low German. Some articles initiate new fields of enquiry, e.g. uncharted areas of dialectology, others give comprehensive reviews of certain domains, e.g. the provenance of Old Frisian law texts, while a third category focusses on specific topics ranging from phonology, grammar and etymology to aspects of Frisian literature and a medieval Frisian ballad.